2015
DOI: 10.1007/s00436-015-4653-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural prevalence in Cuban populations of the lymnaeid snail Galba cubensis infected with the liver fluke Fasciola hepatica: small values do matter

Abstract: Natural infections of lymnaeid snails by Fasciola hepatica are of primary importance to study transmission. Also, infected snails in the field can be used to explore the existing compatibility in host-parasite interactions. This paper aimed to describe the infection rate of Galba cubensis populations in fasciolosis transmission areas. Eight sites were sampled in western Cuba and 24 infected snails at six sites were found. The mean prevalence was 2.94% and the maximum value was 11.4%. The intensity of parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
0
19
2
1
Order By: Relevance
“…; Vázquez et al . ); it is therefore hard to find infected snails in studies such as ours. Moreover Grabner et al .…”
Section: Discussionmentioning
confidence: 73%
“…; Vázquez et al . ); it is therefore hard to find infected snails in studies such as ours. Moreover Grabner et al .…”
Section: Discussionmentioning
confidence: 73%
“…In particular, these results endorse G. cubensis as playing the major role of parasite transmission in the region. This is the case in Cuba where G. cubensis shows high compatibility with F. hepatica both in the laboratory (Vâzquez et al, 2014) and in the field (Vâzquez et al, 2015;Alba et al, 2016) compared to P. columella (Gutiérrez et al 2011). According to Hubendick (1951), G. cubensis has acircum-Caribbean distribution, occurring in most of the West Indies.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of a given parasite in the field is mostly random and linked to that of the intermediate host, which normally has narrower dispersal capacity than definitive host species [ 29 ]. Digenean infection in the intermediate host is a probabilistic event [ 9 ] but chances may increase if high densities of definitive hosts also occur. Therefore, this study was conducted in livestock farms, some of which have been reported as transmission foci of F. hepatica [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…While human fasciolosis is characterised by reduced but repeated outbreaks and few sporadic cases are reported all year round [ 4 , 5 ], it is accepted that the disease is an important veterinary problem [ 4 , 6 , 7 ]. Warm temperatures and frequent rainfall throughout the year favour the existence of two species of lymnaeid snails, Galba cubensis and Pseudosuccinea columella , which act as intermediate hosts of F. hepatica in Cuba [ 8 , 9 ] and other regions of the world [ 10 , 11 ]. The ecological features of G. cubensis (amphibious snail with wide tolerance limits) along with a strong compatibility with Cuban isolates of F. hepatica favour its role as the main intermediate host for this parasite in Cuba [ 12 , 13 ] whereas P. columella plays only a secondary role as intermediate host of F. hepatica in the region [ 13 ].…”
Section: Introductionmentioning
confidence: 99%